Effects of ursodeoxycholic acid and glutathione combination in spleen TNF-α and apoptotic index in rats with cholestasis - Darmawan, Danu; Lestari, Endang Sri; Prasetyo, Sigit Adi; Muniroh, Muflihatul; Prasetyo, Agung Aji (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Cholestasis is a disorder of the formation or flow of bile. Among its contributors, tumour necrosis factor (TNF)-α stands out as the most influential inducer of apoptosis. Meanwhile, ursodeoxycholic acid (UDCA) is a valuable agent with choleretic properties, protecting the hepatobiliary system. Glutathione (GSH) enhances endothelial response and prevents liver fibrosis Objectives: This study evaluates the effect of a combination of GSH-UDCA on splenic TNF-α expression and apoptosis index in Sprague Dawley (SD) rats with cholestasis Methods: This experiment with a post-tests-only control group design involving 28 male SD rats. They were randomly into four groups: group (K) with 20 mg UDCA, group 1 (P1) with 10 mg UDCA + 10 mg GSH, group 2 (P2) was given UDCA 20 mg + GSH 15 mg, and group 3 (P3) was given UDCA 30 mg + GSH 20 mg. Cholestasis was obtained by ligation of the common bile duct through a laparotomy. During three weeks of trial, rats were administered daily with UDCA orally and GSH intramuscularly. On day 22, rats were sacrificed and spleen samples were taken for anatomical pathology examination. Results: There were significant differences in TNF-α expression between groups K vs P3; P1 vs P3, and P2 vs P3 (p=0.002). There was a significant difference in the apoptotic index between groups K vs P1 (p<0.001); K vs P2 (p=0.004), and K vs P3 (p=0.005). Conclusions: The UDCA-GSH combination demonstrated a prophylactic effect in SD rats with cholestasis and might be an effective supplemental therapy with UDCA for cholestatic diseases. The difference in TNF-α expression and apoptotic index was lower in SD rats UDCA-glutathione combination group than single dose UDCA. Between TNF-α and the apoptotic index, there is a moderate positive relation.